Human mesenchymal stromal cells alginate encapsulation beneficial effect for storage at ambient temperature under hypoxic conditions - Hubenia, Oleksandra; Kot, Yuriy; Trufanova, Natalia (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):296